Knowledge networks - Bedford, Denise; Sanchez, Thomas W. (Working methods for knowledge management, 2021)
Networks are essential to mobility - mobility of people, goods, services, communications, and knowledge. The 21st century knowledge economy is dependent upon knowledge mobility and flows. Knowledge networks build upon, but are more complex than, traditional networks. While the network science literature is a starting point, it is not sufficient for modelling or managing knowledge networks. Knowledge networks pay greater attention to nodes as knowledge sources, links as relationships, and the knowledge content of messages. Knowledge Networks describes the role of networks in the knowledge economy, explains network structures and behaviors, walks the reader through the design and setup of knowledge network analyses, and offers a step by step methodology for conducting a knowledge network analysis. Bedford and Sanchez bridge the academic and business perspective of networks. This book illustrates the role of human and non-human actors in these evolving networks, and describes the emerging nature of networks of machines and things. Knowledge Networks is essential reading for business managers, knowledge managers, network analysts, consultants, and researchers in knowledge transfer and translation.